2022
DOI: 10.1101/2022.01.25.477777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-throughput approach to identify reproductive toxicants among environmental chemicals using an in vivo evaluation of gametogenesis in budding yeast Saccharomyces cerevisiae

Abstract: Background: Environmental chemical exposures are likely making important contributions to current levels of infertility and its increasing incidence. Yet the US produces high volumes of industrial chemicals for which there is limited data on their potential human reproduction toxicity. Current assays typically used in policy and regulatory settings involve costly and time- consuming whole-animal rodent tests which limit the rapidity with which one can assess the thousands of chemicals yet to be tested. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…First, 111 chemicals were tested at two concentrations (30 μM and 100 μM) based on the good predictive value of the screens at the highest concentration [ 21 ], with four biological repeats each performed in experimental duplicates. Of these 111 chemicals, a subset of 61 chemicals were further tested at all four concentrations (10 μM, 30 μM, 50 μM and 100 μM) with five biological repeats performed in duplicate in order to facilitate future comparison with a comparable yeast assay [ 22 ] ( Table S1 ). Due to solubility limitations, 21 chemicals were tested at lower concentrations than those indicated ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, 111 chemicals were tested at two concentrations (30 μM and 100 μM) based on the good predictive value of the screens at the highest concentration [ 21 ], with four biological repeats each performed in experimental duplicates. Of these 111 chemicals, a subset of 61 chemicals were further tested at all four concentrations (10 μM, 30 μM, 50 μM and 100 μM) with five biological repeats performed in duplicate in order to facilitate future comparison with a comparable yeast assay [ 22 ] ( Table S1 ). Due to solubility limitations, 21 chemicals were tested at lower concentrations than those indicated ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some of the chemicals were further assessed for the specific stage of meiosis affected and identification of genes and key meiotic processes involved. The yeast assay is based on detecting gamete viability using absorbance measurements to assess the growth of viable gametes through growth curves that shift to the right when the pool of gametes is reduced post exposure [23]. After non-gametes are removed in the assay, the number of viable gametes can be determined by measuring the mitotic growth of living cells that remain in the culture via optical densities at 600 nm (OD 600 ) on microplate readers.…”
Section: Background On Htp Assays (S Cerevisiae and C Elegans)mentioning
confidence: 99%
“…Previous research has shown that these two assays can predict reproductive toxicity rapidly and cost-effectively. Yeast models are an established platform for screening effects on gametogenesis [26], as demonstrated by research from our collective group, which showed how this model can be used to screen for reproductive toxicants, including BPA and its replacement analogs [23]. Similarly, the C. elegans assay has been shown to perform well as a rapid screen for germline toxicants through the induction of aneuploidy [25], a relevant predictor of decreased litter size and ovarian defects in mammalian studies [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; https://doi.org/10.1101/2024.03. 22.584808 doi: bioRxiv preprint takes advantage of the naturally hermaphroditic (XX) state of C. elegans and the naturally low occurrence of males (<0.2%). The appearance of males in the population is often a result of meiotic segregation errors, i.e.…”
Section: Introductionmentioning
confidence: 99%